ACTUAL DESIGN MODEL DEVELOPMENT OF PROTECTIVE SCREEN OVER THE ACTIONS OF SUBWAY LINES (Academic journal Industrial Machine Building Civil Engineering, 2017)
It is given calculation model development results of protective shield overexisting tunnels of subway in influence zone of transport interchange construction  in the city of Minsk. The analysis of modeling problems of the system «construction - soil massif» is performed. It is proposed the approach to development of an adequate design model for complex engineering-geological conditions. An adequate calculation model of the transport interchange site was developed. The applying modern methods results of calculating the system «construction – soil massif» are given. The stress-strain state nature of the tunnel structures at all stages of the transport interchange construction is analyzed. The results of the calculation are compared with the data obtained during testing of the protective screen in full-scale conditions. The special practical significance of using such calculation methods at the design and construction stage of transport facilities is noted.
Keywords: transport facility; calculation model; soil; deformation; stresses